Do children with autism and Asperger's disorder have difficulty controlling handwriting size? A kinematic evaluation. (March 2015) - Johnson, Beth P.; Phillips, James G.; Papadopoulos, Nicole; Fielding, Joanne; Tonge, Bruce; Rinehart, Nicole J.
Highlights: Previous studies indicate children with ASD have difficulty controlling handwriting size. We kinematically assessed the control of handwriting size in ASD using writing guides. We found that control of size of fundamental handwriting movements was intact. Some abnormalities in controlling velocity of movement at 40 mm were identified. There was no difference in neuromotor noise between ASD and TD children. Abstract: Children with autism spectrum disorders (ASD) often show difficulties in controlling letter size and consistent letter formation during handwriting; however, there has been little research into the underlying nature of handwriting impairments in this group. The aim of this study was to assess the ability of children with ASD to regulate the size and consistency of fundamental handwriting movements when using writing guides, and determine whether the kinematic profile during writing is different to typically developing children. Twenty-six boys with ASD (16 with high-functioning autism, 10 with Asperger's disorder) aged 8–13 years (IQ > 75), and 17 typically developing children wrote a series of four cursive letter l 's using 10 mm and 40 mm writing guides, using a graphics tablet and stylus. Movement size and consistency was comparable between groups when the writing guides were set at 10 mm; however, handwriting movements of children with ASD were significantly faster and more fluent than typically developing children when writing guides were set at 40 mm. Neuromotor noise was comparable to that of typically developing children across both writing sizes. Clinically, our findings indicate that children with ASD have a well-automated motor plan for simple handwriting movements when writing guides are present and that problems of handwriting legibility in ASD are likely to arise from other factors, such as complex motor chaining (i.e. writing whole words and sentences), or attentional, working memory and linguistic demands when writing.